Rancang Bangun Alat Alarm Peringatan Hujan dengan Menggunakan Sensor Raindrop Untuk Petani - Erlangga Bayu Yudho Prakoso; Dista Dian Saputri; Dhian Joedhistiro; Egie Irawan; Rudi Susanto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Rain for rice farmers is a blessing. When the harvest season arrives, there are still many farmers who dry the harvested grain in their yards or even on the streets. There are many incidents, if it rains and farmers who dry their grain late to secure it from rain. Several incidents of wet grain due to rain, due to the complacency of grain drying farmers, one of which fell asleep due to achievement. The rain warning alarm using the raindrop sensor aims to warn of rain or the possibility of rain. The method in making this warning alarm is through the study of literature. The results of the test of the tool showed that the tool made could provide a warning of rain by using air humidity, temperature, and pressure parameters. From the research and testing of the device, it can be concluded that the increase in humidity, the decrease in temperature, and the decrease in pressure contribute to the occurrence of rain.